A screening methodology for building multiple energy retrofit measures package considering economic and risk aspects. (20th January 2019) - Zheng, Donglin; Yu, Lijun; Wang, Lizhen; Tao, Jiangang
Abstract: In recent years, more and more existing building has an ever increasing requirement of retrofit, which has been developed from individual measure to combination package of multiple measures. It has become the challenging task for screening building multiple energy retrofit measures package (BMERMP). In this paper, a stepwise screening methodology for BMERMP is proposed considering economic and risk aspects, which integrates Life-Cycle Cost (LCC) and Monte Carlo (MC) analysis. First of all, this paper puts forward a calculation reference table for energy saving retrofit potential. In addition, this paper also uses unit energy saving incremental cost (UESIC) to screen technology and suggests economic internal rate of return（EIRR）as cost-benefit analysis index of BMERMP. Furthermore, the authors propose the concept of Value-at-Risk (VaR) as an effective measure to control the risk. The VaR for EIRR is determined by risk variation and can be obtained through MC simulation. Meanwhile, the study takes a commercial building for example, this building comprises 19 measures in initial BMERMP by energy diagnosis and the VaR of initial BMERMP is 97.6%, which has a high risk. According to the ranking of UESIC value, when 4 high cost technologies are reduced, the VaR can be reduced to 0.07%, then the economy of BMERMP is feasible and the risk is controllable. This paper provides a new perspective for the decision maker to select BMERMP. Highlights: A stepwise screening methodology to select building multiple energy retrofit measures package (BMERMTP) is proposed. The screening methodology integrate Life-Cycle Costing(LCC) and Monte Carlo(MC) analysis. Cost-benefit analysis for BMERMTP adopt the economic benefits of energy retrofits in the economic period. Present the concept of Value-at-Risk (VaR) as an effective measure to control the risk for BMERMTP. It suggests calculation table for building energy-saving retrofit potential.